KAJIAN EVAPOTRANSPIRASI POTENSIAL STANDAR PADA DAERAH IRIGASI MUARA JALAI KABUPATEN KAMPAR PROVINSI RIAU - Djuang Panjaitan (Universitas Pasir Pengaraian, 2012)
The aim of this research was comparison of refererence evapotranspiration of non standard andstandard using method was recommended FAO at Muara Jalai Irrigation Area, Kampar District, RiauProvince. Method was used used to analyze non standard evapotranspiration using Penman Modification sothat standard evapotranspiration using Penman Monteith by climatological data such as temperature, windspeed, humidity and sunshine in Pasar Kampar Station at year 1999 to 2010. The result of this researchprove that evapotranspiration potencial standard using Penman Monteith produces more than less 18% ofaverage value if compare with evapotranspiration potencial non standard using Penman Modification atMuara Jalai Irrigation Area, Kampar District